Bilateral Acute Retinal Necrosis: Clinical Features and Outcomes in a Multicenter Study. (3rd October 2019) - Miserocchi, Elisabetta; Iuliano, Lorenzo; Fogliato, Giovanni; Modorati, Giulio; Couto, Cristobal; Schlaen, Ariel; Hurtado, Erika; Llorenç, Victor; Adan, Alfredo; Bandello, Francesco
ABSTRACT: Purpose : To describe clinical features and outcome in bilateral acute retinal necrosis (BARN). Methods : Observational retrospective longitudinal review of ocular findings. Results : Thirty eyes of 15 patients (age 44.1 ± 15.8). Delay of involvement between eyes was 57.2 ± 105.2 months (median 3, range 0.5–360). Herpes simplex virus (HSV)-1 was the most frequent (20 eyes, 66.6%), followed by HSV-2 (five eyes, 16.7%) and varicella zoster virus (VZV, four eyes, 13.3%). Visual acuity worsened in 7 (23%) eyes, improved in 4 (13%), and remained stable in 19 (63%). Major complications included retinal detachment (11 eyes, 36%), optic atrophy (11 eyes, 33%), proliferative vitreoretinopathy (four eyes, 13.3%), neovascular glaucoma (four eyes, 13.3%), phthisis bulbi (three eyes, 10%). Symptoms-to-referral average time was 2.7 ± 1.0 weeks (range 1–4). Conclusions : In our study BARN was associated with severe visual outcome and high rate of ocular complications. Although BARN is a rare disease, the course is aggressive, regardless prompt referral in tertiary-care uveitis centers.